2016
DOI: 10.1080/17445647.2016.1264319
|View full text |Cite
|
Sign up to set email alerts
|

Changes in glacier surface cover on Baltoro glacier, Karakoram, north Pakistan, 2001–2012

Abstract: The presence of supraglacial debris on glaciers in the Himalaya-Karakoram affects the ablation rate of these glaciers and their response to climatic change. To understand how supraglacial debris distribution and associated surface features vary spatially and temporally, geomorphological mapping was undertaken on Baltoro Glacier, Karakoram, for three timeseparated images between 2001-2012. Debris is supplied to the glacier system through frequent but small landslides at the glacier margin that form lateral and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…This suggests that it is the average size of cliffs that increases in the melt season. Ponded area accounts for less than 1.1% (±0.2%) of the debris-covered area in all dry seasons and increases up to 2.1% (±0.4%) during the wetter seasons when ponds fill (Miles andothers, 2016, 2017b). Contrary to ice cliffs it is the number of ponds that increases in the wetter seasons suggesting new formations with increased melting activity (Table 3).…”
Section: The Inventorymentioning
confidence: 99%
“…This suggests that it is the average size of cliffs that increases in the melt season. Ponded area accounts for less than 1.1% (±0.2%) of the debris-covered area in all dry seasons and increases up to 2.1% (±0.4%) during the wetter seasons when ponds fill (Miles andothers, 2016, 2017b). Contrary to ice cliffs it is the number of ponds that increases in the wetter seasons suggesting new formations with increased melting activity (Table 3).…”
Section: The Inventorymentioning
confidence: 99%
“…The greatest percentage change in supraglacial water body number (73 %) and area (171 %) occurred between 2001 and 2004. Increase in supraglacial water body area and number has previously been attributed to changes in precipitation since 2000 (Quincey et al, 2009;Gibson et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The debris layer is thinnest (0.01-0.15 m) in the upper ablation area of the glacier and exceeds 1 m at the glacier terminus (Mihalcea et al, 2008b). Supraglacial debris units have differing lithologies across the debris-covered glacier surface, which include granite, schist, gneiss and metasediments (Gibson et al, 2016). …”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Bocchiola and Diolaiuti (2013) and Hewitt (2005) observed that the glaciers in the central and eastern Himalayas, Hindu-Kush and Karakoram, shows different trends of advance, stable or retreat, which is known as "Karakoram Anomaly". This anomalous behavior can be attributed to supra glacier debris cover and lack of mass balance data (Gibson et al, 2017;Scherler et al, 2011a). Aim of this study is to evaluate the temporal dynamics of glaciers using the Landsat images and weather data, in northern Pakistan.…”
Section: Introductionmentioning
confidence: 99%